Sistem Hukum Penanggulangan Darurat Kesehatan dalam Perspektif Omnibus Law: Relasi terhadap Hak Asasi Manusia - Fradhana Putra Disantara; Fathul Hamdani; Ana Fauzia; Geraldha Islami Putra Disantara (Jurnal Interpretasi Hukum, 2024)
The purpose of this research is to examine various problems in overcoming the past health emergency (Covid-19 pandemic), and to initiate the use of the concept of omnibus law in the context of harmonizing the legal system for overcoming health emergencies with a human rights perspective. This research applies the normative research method using statutory, conceptual, and case approaches. The results show that the current regulation on health emergency management is still not comprehensive enough to guarantee legal certainty and protection of human rights. For example, the authority to determine regional quarantine in the hands of the Central Government is in fact not very effective, because each region in Indonesia has its own characteristics, so it would be better to apply regional quarantine asymmetrically by handing over the authority to determine regional quarantine to local governments who know better the real conditions in their regions. Then in terms of procurement and implementation of vaccinations, starting from the absence of legal certainty and protection to obtain halal-certified products (vaccines) as mandated in Law Number 33 of 2014 concerning Halal Product Guarantee, to the imposition of sanctions for delaying or terminating social security which actually contradicts Law Number 40 of 2004 concerning the National Social Security System. Therefore, it is necessary to harmonize the legal instruments for health emergency management using the concept of omnibus law which will revise all regulations related to the acceleration of infectious disease prevention, such as the implementation of regional quarantine, the application of sanctions, guarantees of community needs, to regulations related to the implementation of vaccinations.